2015
DOI: 10.1371/journal.pone.0123444
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein Levels in Blood Plasma Decline with Healthy Aging

Abstract: There is unequivocal evidence that alpha-synuclein plays a pivotal pathophysiological role in neurodegenerative diseases, and in particular in synucleinopathies. These disorders present with a variable extent of cognitive impairment and alpha-synuclein is being explored as a biomarker in CSF, blood serum and plasma. Considering key events of aging that include proteostasis, alpha-synuclein may not only be useful as a marker for differential diagnosis but also for aging per se. To explore this hypothesis, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 82 publications
4
25
1
1
Order By: Relevance
“…2,9 However, usefulness and reproducibility of these techniques have been questioned, 18 and variable a-syn expression may depend, among others, on age. 19 We have also to reiterate that the study was limited to the mucosa and that, theoretically, submucosal studies could have shown features differentiating PD patients from controls. In summary, both total and phosphorylated a-syn is found similarly in the mucosa of PD patients and in controls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…2,9 However, usefulness and reproducibility of these techniques have been questioned, 18 and variable a-syn expression may depend, among others, on age. 19 We have also to reiterate that the study was limited to the mucosa and that, theoretically, submucosal studies could have shown features differentiating PD patients from controls. In summary, both total and phosphorylated a-syn is found similarly in the mucosa of PD patients and in controls.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies proposed further biopsy processing, including acidification or paraffin‐embedded tissue blots . However, usefulness and reproducibility of these techniques have been questioned, and variable α‐syn expression may depend, among others, on age . We have also to reiterate that the study was limited to the mucosa and that, theoretically, submucosal studies could have shown features differentiating PD patients from controls.…”
Section: Discussionmentioning
confidence: 98%
“…Another study revealed that α-synuclein levels in blood plasma from healthy individuals markedly decrease between the 3rd and 5th decade of life29. Salivary α-synuclein may not only be a potiential marker for diagnosis but also reflect biological age and qualify as a candidate biomarker of aging to advance life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we mainly evaluated the neurotoxicity of A53T mutant α‐syn, with WT α‐syn as a control to compare their possible difference in stimulation effect; (b) Doses and time‐points of stimulation. The varied physiological concentrations of α‐syn in blood and CFS are detected at nanogram/milliliter level (Koehler et al., ; Lin et al., ), which are up to tenfold in serum and plasma and up to 10,000‐fold higher in whole blood due to its abundant expression in hematopoietic system (Mollenhauer et al., , ). Previous studies in vitro show a range of concentrations of α‐syn available from 0.1 to 10 μg/ml at one time‐point (24 hr) (Roodveldt et al., , ).…”
Section: Methodsmentioning
confidence: 99%